2017
DOI: 10.1242/jeb.164400
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to CO2 influences metabolism, calcification, and gene expression of the thecosome pteropodLimacina retroversa

Abstract: Thecosomatous pteropods, a group of aragonite shell-bearing zooplankton, are becoming an important sentinel organism for understanding the influence of ocean acidification on pelagic organisms. These animals show vulnerability to changing carbonate chemistry conditions, are geographically widespread, and are both biogeochemically and trophically important. The objective of this study was to determine how increasing duration and severity of CO treatment influence the physiology of the thecosome , integrating bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
70
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(79 citation statements)
references
References 76 publications
9
70
0
Order By: Relevance
“…While juveniles showed reduced calcification at low ar (Comeau et al, 2010a;Bednaršek et al, 2017), an increase in calcification was seen in the less sensitive adults of L. retroversa (Maas et al, 2018). Experimentally derived LOE ranged from ar = 1.25 for 3 days (Comeau et al, 2010a) to ar = 1.02 for 1-3-week duration (Maas et al, 2018), which coincides with a significant calcification decline also in Heliconoides inflatus (Moya et al, 2016). These duration-dependent thresholds were validated with a field-derived changepoint of ar = 1.02 (SE = 0.07; Bednaršek et al, 2017).…”
Section: Calcificationmentioning
confidence: 89%
See 2 more Smart Citations
“…While juveniles showed reduced calcification at low ar (Comeau et al, 2010a;Bednaršek et al, 2017), an increase in calcification was seen in the less sensitive adults of L. retroversa (Maas et al, 2018). Experimentally derived LOE ranged from ar = 1.25 for 3 days (Comeau et al, 2010a) to ar = 1.02 for 1-3-week duration (Maas et al, 2018), which coincides with a significant calcification decline also in Heliconoides inflatus (Moya et al, 2016). These duration-dependent thresholds were validated with a field-derived changepoint of ar = 1.02 (SE = 0.07; Bednaršek et al, 2017).…”
Section: Calcificationmentioning
confidence: 89%
“…This implies variable control over calcification processes, likely because calcification is energetically expensive when sustained at low ar gradients (Lischka et al, 2011;Bednaršek et al, 2017). While juveniles showed reduced calcification at low ar (Comeau et al, 2010a;Bednaršek et al, 2017), an increase in calcification was seen in the less sensitive adults of L. retroversa (Maas et al, 2018). Experimentally derived LOE ranged from ar = 1.25 for 3 days (Comeau et al, 2010a) to ar = 1.02 for 1-3-week duration (Maas et al, 2018), which coincides with a significant calcification decline also in Heliconoides inflatus (Moya et al, 2016).…”
Section: Calcificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Our measured pteropod CA activity is comparable to that of diatoms (1–2 × 10 −7 CA/POC; Table ), despite not using the enzyme for photosynthesis or in a traditional carbon‐concentrating mechanism (Hopkinson et al ). Instead, pteropods, like corals, most likely use CA for biomineralization (Tambutte et al ; Maas et al ). Because of the longevity of CA we have documented here, it is possible that CA produced by pteropods could still be active after the pteropods have died and are sinking through the water column, where corrosive carbonic acid will start to dissolve their aragonite shells.…”
Section: Discussionmentioning
confidence: 99%
“…Manno et al, 2017). The impact of predicted future conditions on live specimens has been assessed using wide variety of parameters, including calcification (Comeau et al, 2009(Comeau et al, , 2010Maas et al, 2018;Moya et al, 2016), shell degradation (Bednaršek et al, 2012b;Bergan et al, 2017;Lischka and Riebesell, 2012), metabolic rates (Maas et al, 2011;Seibel et al, 2012), respiration (Comeau et al, 2010;Maas et al, 2018;Moya et al, 2016), and gene expression patterns (Koh et al, 2015;Maas et al, 2015Maas et al, , 2018Moya et al, 2016;Thabet et al, 2017). Generally, previous studies have found that as the aragonite saturation state decreases, pteropod calcification rates decrease (Comeau et al, 2010(Comeau et al, , 2009Lischka and Riebesell, 2012).…”
Section: Understanding Natural Pteropod Variabilitymentioning
confidence: 99%